PENGARUH LUAS LAHAN, PRODUKSI DAN KURS TERHADAP VOLUME EKSPOR KAKAO DI INDONESIA - Padang, Debora; Abbas, Tarmizi; Rahmah, Mutia; Trisniarti, Noviami (LPPM Universitas Malikussaleh - Indonesia, 2025)
Indonesia is one of the largest cocoa producers in the world. The volume of Indonesian cocoa exports tends to be stable, although various factors influence annual fluctuations. Cocoa is a leading commodity in the plantation sector that can support the Indonesian economy, significantly impacting economic growth. This research was conducted in Indonesia and aims to analyse the influence of government land area, private land area, production, and exchange rate on Indonesian cocoa export volume. The data used is secondary data (time series) for 33 years from 1990 to 2023, obtained from the Central Statistics Agency and the World Bank. This study uses the multiple linear regression analysis method. The study results indicate that the government land area, production, and exchange rate partially have a positive and significant effect on the volume of cocoa exports in Indonesia. Partially, the private land area does not affect the volume of cocoa exports in Indonesia. Simultaneously, the government land area, private land area, production, and exchange rates positively and significantly affect the volume of cocoa exports in Indonesia. The results of the analysis indicate the importance of improving the factors influencing the volume of cocoa exports in Indonesia to encourage export activities to excel in the international market.